Gender Perspective and Women's Challenges in Public Relations - Maharani, Blangi Intan; Sembiring, Putri Sosanti; Dwianita, Dwianita (Journal Analytica Islamica, 2025)
As time progresses, women play an increasingly important role in improving the quality of both public and domestic sectors. Generally, gender issues that become the main topic of discussion revolve around the status and position of women in society, which are still often viewed as subordinate or marginal. The significant rise in the number of female practitioners in the public relations (PR) industry has led to the perception that women have experienced gender discrimination in Indonesia. This journal aims to analyze and examine gender perspectives on women in the field of public relations, the impact of the feminization of the PR profession, as well as the challenges faced by women in carrying out their roles as public relations practitioners. The results of this literature study indicate that male practitioners are more likely to hold managerial positions than female practitioners. Although the number of female practitioners has exceeded that of males, their status and roles in PR practice remain subordinate to men. Furthermore, there are relevant glass ceiling barriers, including an unequal distribution of tasks, which prevent women from fully demonstrating their potential in the workplace.